Acute management of hyperlipaemic pancreatitis: a successful reduction in triglyceride levels with simultaneous insulin infusion and plasma exchange. Issue 1 (15th March 2016) - Korb, A; Sonnekus, PH; Botha, JD
Abstract : We report on a case in which a combination of an insulin infusion and plasma exchange were successfully used in the acute management of hyperlipaemic pancreatitis.